Efektivitas Kepemimpinan Kepala Sekolah dalam Manajemen Konflik - Deti Rostini; Khalifaturramah khalifaturramah; Sulaiman Sulaiman; Norsyam Amaly (LP. Ma'arif Janggan Magetan, 2023)
The principal plays an important role in influencing and directing existing school personnel. This is done so that the plans that have been determined can be carried out by involving all elements (cooperating) in achieving school goals. Teacher performance in the form of carrying out the task of educating students is determined by work motivation. Therefore, effective principal leadership can influence teacher work. This study aims to determine the effectiveness of the principal's leadership in managing conflicts that occur in SMPN X Banjar, South Kalimantan. This study uses a qualitative paradigm. While the approach is a case study. Methods of data collection using observation, interviews, and documentation studies. The results of the study show that democratic principal leadership (having principal competence) is able to minimize conflicts that occur within the school environment.